2022
DOI: 10.3389/fenvs.2021.793005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poplar Ecological Retreat on Habitat Suitability for Migratory Birds in China’s Dongting Lake Wetland

Abstract: The Poplar Ecological Retreat (PER) project in Dongting Lake wetland is an important measure in response to China’s ecological civilization construction policy, it aims to remove eastern cottonwoods (Populus deltoides) that artificial large-scale planted in this area and restore the natural state of the wetland, and has got a lot of attention by society and scholars. However, as one of the most important wintering place for migratory birds in the world, the impact of PER on migratory bird habitats in Dongting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Previous studies have reported that wildlife can also affect the properties of soil ( Elhottová et al, 2012 ). Poplar blocked the landing of migratory birds, crowding out the habitat of wintering migratory birds ( Qu et al, 2022 ). The poplar planting method of digging trenches and lifting ridges made the ground ravine crisscross, which leads to the destruction of fish spawning and migration channels ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported that wildlife can also affect the properties of soil ( Elhottová et al, 2012 ). Poplar blocked the landing of migratory birds, crowding out the habitat of wintering migratory birds ( Qu et al, 2022 ). The poplar planting method of digging trenches and lifting ridges made the ground ravine crisscross, which leads to the destruction of fish spawning and migration channels ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2020) also reported that water deficiency would lead to a decrease in microbial abundance. After the implementation of the PER project, the restoration of wildlife populations and plant diversity injected more organic matter into the soil, resulting in an increase in the diversity of microbial community structures, as the SOM is an essential substrate for microbial survival (Marshman and Marshall, 1981;Yu et al, 2022). These soil characteristics can regulate nutrients and anaerobic or aerobic processes in the soil to affect microbial metabolism, and then change the community structure of microorganisms (Gutknecht et al, 2006;Card and Quideau, 2010).…”
Section: Response Of Bacterial Community Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The list of protected species can be continuously updated in the future based on the list of threatened species identi ed by the study. Moreover, the assessment of priority areas for restoring habitats for migratory birds is not static, and the impact of the EDS on the importance of migratory birds needs adjustment (Qu et al, 2022;Tang et al, 2016). Limited by the acquisition of geospatial data and species survey data, this study considered only habitat restoration of migratory birds in PYL and DTL wetlands under the EDS.…”
Section: Limitations and Prospectsmentioning
confidence: 99%